2020
DOI: 10.3389/fonc.2020.00259
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanism of ITGBL1 in the Metastasis of Colorectal Cancer

Abstract: Integrin, beta-like 1 (ITGBL1) protein is located in the extracellular matrix (ECM) and involved in the development and metastasis of many tumors. However, the regulatory mechanism of ITGBL1 in colorectal cancer (CRC) remains unclear. This study was to analyze the expression profile of CRC and to identify the expression change of ITGBL1 gene at different stages of CRC. Survival analysis showed that ITGBL1 was related to the metastasis of CRC, and CRC patients with a high expression of ITGBL1 had earlier metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…A recent publication has also proposed the significant role of syntrophin beta 1-SNTB1 as prognostic marker for colon cancer metastasis (26). Moreover, it has been found that integrin betalike 1 -ITGBL1 is involved in the colon cancer development and metastasis (27) whileTACSTD2 and LEMD1 belong to the significant up-regulated genes of colon cancer (28,29). For the case of under-expressed MEGs found in our analysis, it has been indicated that the lower levels of PPARGC1A and SLC26A2 could increase colon cancer risk, proliferation and propagation and they have been proposed as possible candidate targets for cancer therapy (30,31).…”
Section: Discussionmentioning
confidence: 98%
“…A recent publication has also proposed the significant role of syntrophin beta 1-SNTB1 as prognostic marker for colon cancer metastasis (26). Moreover, it has been found that integrin betalike 1 -ITGBL1 is involved in the colon cancer development and metastasis (27) whileTACSTD2 and LEMD1 belong to the significant up-regulated genes of colon cancer (28,29). For the case of under-expressed MEGs found in our analysis, it has been indicated that the lower levels of PPARGC1A and SLC26A2 could increase colon cancer risk, proliferation and propagation and they have been proposed as possible candidate targets for cancer therapy (30,31).…”
Section: Discussionmentioning
confidence: 98%
“…Accumulating evidence indicated that ITGBL1 was crucial in carcinogenesis and cancer progression. Multiple studies showed that ITGBL1 functioned as an oncogene [22,23]. For example, in acute myeloid leukemia (AML), ITGBL1 methylation was reported to have an impact on prognosis, and patients with hypermethylation of ITGBL1 tended to have leukemia-free survival and shorter OS [24].…”
Section: Discussionmentioning
confidence: 99%
“…Based on in-silico analysis of gene expression data from colorectal cancer Qi et al proposed ITGBL1-related protein–protein interaction network [ 19 ]. It consists of a dozen or so of ITGBL1 binding proteins, among them three (FN1, CTNNB1, COL1A1) which could provide a link with extracellular Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We were the first to report in 2013 that ITGBL1 overexpression stimulates ovarian cancer cell migration rate [ 12 ]. Later, since 2015, there have arisen a dozen or so reports concerning the ITGBL1 role in several human diseases, e.g., breast cancer [ 13 ], non-small cell lung cancer (NSCLC) [ 14 , 15 ], HBV-related liver pathologies [ 16 , 17 ], pulmonary fibrosis [ 15 ], osteoarthritis [ 18 ], colorectal [ 19 , 20 , 21 ], gastric [ 22 ], prostate [ 23 ] and ovarian cancer [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation